PEEK/graphite film formation on microgrooves of PEEK- hybrid radial Al2O3 ball bearings under rolling contact in dry condition. (August 2022) - Koike, Hitonobu; Kida, Katsuyuki; Mizobe, Koshiro; Matsumura, Toshihiko; Inagaki, Masahiro
Abstract: The influence of PEEK (Polyether ether ketone) composite solid lubricant film on hybrid radial polymer bearing life, consisting of PEEK ring-PTFE (polytetrafluoroethylene) /graphite retainer-alumina balls, was investigated in terms of self-lubrication properties. A PEEK/graphite film layer formed around the 'pure rolling contact' track in the Hertzian contact area of the PEEK ring during rolling contact under dry conditions, and then covered the whole contact track. The PEEK/graphite film growth maintained smooth rotation of the bearings, avoiding seizure. Microgrooves on the PEEK ring strongly influenced the formation of PEEK/graphite film. This result helps effective tribological design of micro grooves for polymer bearings.